FAKTOR YANG MEMPENGARUHI PE RMINTAAN BERAS ANAK DARO (STUDI KASUS PERUMAHAN PANDAU PERMAI KABUPATEN KAMPAR) - Desriani, Rezky; Edwina, Susy; Khaswarina, Shorea (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Rice is the staple food of Indonesian people generally as well as Riau society particularly. The high number of rice consumption is influenced by the high number of Indonesian population. The nutrient in rice becomes the consideration for the society in choosing rice. Based on the survey the rate of rice consumption in Riau continues to increase every year. The research was conducted in Pandau Permai Housing, Kampar Regency. Pandau Jaya village is included as Kampar Regency area with the area of ​​14,274 hectares. Total population in Pandau Jaya Village is 33,100 that consist of 17,040 female and the male is 16,060 inhabitants. The purposes of this study are: (1). To analyze factors affecting the demand for Anak Daro rice in Pandau Permai housing (2). To analyze dominant factor affecting the demand for Anak Daro rice in Pandau Permai housing. The data were obtained from interview towards the respondents who consume Anak Daro rice. The analytical method that was used in the study was the analysis of multiple linear regressions. The factors included in the study were age factor (X1), education (X2), the number of dependents (X3), the price of Anak Daro rice (X4), other rice prices (X5), and income (X6). The result indicate that factor toward the demand for Anak Daro rice is the number of dependents. The dominant factor toward the demand for Anak Daro rice is X3 with the value of regression coefficient of 4,376. Keywords:  anak daro rice, demand, rice,